Reducing potential aerosol generation in flexible nasolaryngoscopy: a novel method. Issue 8 (9th August 2020) - Curran, J; Calder, N; Yaneza, M; Iyer, A
Abstract: Background: Fibre-optic nasoendoscopy and fibre-optic laryngoscopy are high-risk procedures in the coronavirus disease 2019 era, as they are potential aerosol-generating procedures. Barrier protection remains key to preventing transmission. Methods: A device was developed that patients can wear to reduce potential aerosol contamination of the surroundings. Conclusion: This device is simple, reproducible, easy to use, economical and well-tolerated. Full personal protection equipment should additionally be worn by the operator.